Instagram for English Language Learning: Learners’ Views on Reading Comprehension through Captions, Threads, and Comments - Puspa, Adelia; Saputra, Dwi Bayu; Marpaung, Tiara Azzahra; Citra Sari Dewi, Anggun (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2026)
Although interest in social media–mediated language learning is increasing, most research on Instagram has focused on productive skills, with limited attention to its potential for supporting reading comprehension, especially through platform-specific textual features. This study addresses this gap by critically examining the ways in which captions, comments, and threads mediate English as a Foreign Language (EFL) learners’ reading comprehension and engagement in a multimodal digital environment. Using a mixed-methods approach, data were collected from 72 undergraduate students via pre- and post-intervention questionnaires and follow-up interviews following an eight-week Instagram-based extensive reading program. The results indicate a measurable increase in learners’ engagement and perceived comprehension. A majority of participants reported higher engagement (58.4%) and enjoyment (62.5%), while 77.8% noted improvement in reading comprehension. Furthermore, 87.5% of students identified visual-textual integration as a key facilitator of meaning-making, and 70.8% highlighted the comment section as the most effective feature for interpretive support, emphasizing the importance of socially mediated interaction. Qualitative data further demonstrate that comprehension is constructed through the dynamic interplay of multimodal cues, contextual inference, and peer negotiation of meaning, although linguistic informality, such as slang, continues to present challenges. These findings challenge traditional text-centric models of reading by conceptualizing comprehension as a socially situated and multimodal process. The study advocates for a pedagogical shift that incorporates platform-specific affordances of social media into EFL reading instruction, thereby aligning formal educational practices with learners’ digital literacy environments.